2004
DOI: 10.1002/pi.1689
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of the pair maleic anhydride–dicyclopentadiene: I. Copolymerization and post‐copolymerization at high conversion

Abstract: The present study describes the kinetic investigation of the complex binary copolymerization system maleic anhydride (MA)—dicyclopentadiene (DCPD). All syntheses were carried out in homogeneous solution; high conversions in soluble and linear copolymer are achievable when starting from an equimolecular monomer feed. Excess of DCPD would limit the attainable conversions, while surplus of MA would induce crosslinking of the copolymers. The findings of the thorough kinetic study were sustained by structural asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The earlier two papers dedicated to this topic (3,4) presented rather contradictory results; moreover, the conclusions regarding either the reaction mechanism, or the structure of the products obtained are completely different. Recent studies published by us (1,5) have only partially confirmed Gaylord's or Rzaeva's reports. Even if cross propagation represents an important step, nevertheless, the classical models (with or without CTC) cannot satisfactorily describe the abovementioned process.…”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…The earlier two papers dedicated to this topic (3,4) presented rather contradictory results; moreover, the conclusions regarding either the reaction mechanism, or the structure of the products obtained are completely different. Recent studies published by us (1,5) have only partially confirmed Gaylord's or Rzaeva's reports. Even if cross propagation represents an important step, nevertheless, the classical models (with or without CTC) cannot satisfactorily describe the abovementioned process.…”
Section: Introductionsupporting
confidence: 51%
“…Intrinsic viscosities measured for the reaction products are within the range 4 4 8 ml/g, regardless the composition and/or conversion. According to some previous studies (1,5), these values would correspond to M n being placed between 2 Ã 10 3 and 3 Ã 10 3 . Consequently, measuring N percentage in copolymer gives quite accurately, its structure, written as R 0 (MA) n1 (DCPD) n2 .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations